Moving Beyond Normal Accidents and High Reliability Organizations: A Systems Approach to Safety in Complex Systems - Leveson, Nancy; Dulac, Nicolas; Marais, Karen; Carroll, John (Organization studies, 2009)
In this century society faces increasingly large-scale accidents and risks emerging from our own wondrous technologies. Two prominent organizational approaches to safety, Normal Accident Theory and High Reliability Organizations, have focused attention on a variety of industries that deal with hazardous situations, developed concepts to explicate organizational structure and culture, and debated whether accidents are inevitable in complex systems. We outline these approaches and identify some limitations, including narrow definitions, ambiguity about key concepts, confusion of reliability and safety, and overly pessimistic or optimistic conclusions. We believe that the debate between NAT and HRO can become a more productive three-way conversation by including a systems approach to safety emerging from engineering disciplines. The more comprehensive systems approach clarifies the strengths and weaknesses of NAT and HRO and offers a more powerful repertoire of analytic tools and intervention strategies to manage and control post modern risk in complex, high-tech, systems with their potential for catastrophic disruptions and losses.